Civic Learning, Democratic Citizenship and the Public Sphere edited by Gert Biesta, Maria De Bie, Danny Wildemeersch. - Biesta, Gert.; Biesta, Gert.; De Bie, Maria.; De Bie, Maria.; Wildemeersch, Danny.; Wildemeersch, Danny. (Springer Netherlands : Imprint: Springer, 2014)
This books explores the relationships between learning, democratic citizenship and the public sphere from thee interconnected angles: theory, methodology and research. The main message of the book is that civic learning necessarily has a public character, as it is learning that emerges from engagement in democratic processes and practices that occur both at the centre and the margins of society. Through a combination of theoretical development, methodological reflection and empirical case study, the chapters in the book provide new insights in the complexities of learning in the context of the ongoing struggle for democracy.